A simple articulator for maxillofacial prosthetics - Mohamed Behanam; R Haribabu; A Anuroopa (Wolters Kluwer Medknow Publications, 2009)
In patients with a defective maxillo-mandibular complex, the foremost challenge in achieving an accurate centric or eccentric record is the sheer irregularity and non-repeatability of the movements of the mandible. As a result, mandatory clinical procedures like jaw relations, intra or extra-oral tracings and interocclusal records are made complicated, and the accuracy of such records, questionable. Hence every maxillofacial patient must be considered on an individual basis and rehabilitation procedures customized to suit the clinical situation, rather than strictly adhering to theoretical principles. This involves procedures like customizing the record bases, occlusal schemes and individualized training regimens for these patients, along with some modifications in the existing articulators. One such modified articulator is presented here.